A LITERATURE STUDY OF FINANCIAL STATEMENT FRAUD DETECTION - Yessy Yuliana; Agusti Hartono; Alvin Fernando; Carmel Meiden; Prima Apriwenni; Nurlela Nurlela; Yosef Dema (Bajang Institute, 2022)
This research attempts to give an overview of the focus and methods utilized to identify financial statements in Indonesia. This study employed the systematic literature review (SLR) methodology to analyze how the literature on financial reporting develops. Keywords like